Factors Determining The Financial Performance Of Malaysian Private Higher Educational Institutions (PHEI) - Ong , Seng Fook (2008)
The overall goal of this thesis is to study the resources and capabilities of PHEI that form the basis of competitive advantage of PHEI which in turn affects their financial performance and service quality.